Based on Activation of p62-Keap1-Nrf2 Pathway, Hesperidin Protects Arsenic-Trioxide-Induced Cardiotoxicity in Mice - Jia, Yuxin; Li, Jing; Liu, Panpan; Si, Mingdong; Jin, Yanyu; Wang, Hongfang; Ma, Donglai; Chu, Li (Frontiers in Pharmacology, 2021)
Background: Hesperidin (HES) is a flavonoid glycoside found in the tangerine peel and has antioxidant properties. Arsenic trioxide (ATO) is an anti-tumour drug; however, its serious cardiotoxicity limits its clinical application. In addition, the protection of HES against ATO-induced cardiotoxicity has not been explored. Objective: The study aims to investigate and identify the underlying effect and mechanism of HES on ATO-induced cardiotoxicity. Methods: Fifty mice were randomly assigned to five groups. Mice were orally given HES:100 or 300 mg/kg/day concurrently and given ATO intraperitoneal injections: 7.5 mg/kg/day for 1 week. Blood and heart tissues were collected for examination. Evaluated in serum was the levels of creatine kinase (CK), lactate dehydrogenase (LDH) and cardiac troponin I (cTnI). In addition, evaluated in heart tissues were the levels of reactive oxygen species (ROS), superoxide dismutase (SOD), malondialdehyde (MDA), glutathione (GSH), catalase (CAT), tumour necrosis factor-α (TNF-α), interleukin-6 (IL-6), B-cell lymphoma-2 (Bcl-2), Bcl-2-associated X protein (Bax), Caspase-3, cleaved-Caspase-3, p62, Kelch-like ECH-associated protein 1 (Keap1), and nuclear factor erythroid 2-related factor 2 (Nrf2). The heart tissues were also examined for histopathology and mitochondrial ultrastructure. Results: Compared with the ATO group, the HES treatment groups reduced the levels of CK, LDH, cTnI, ROS, MDA, TNF-α, IL-6, Bax, Caspase-3, cleaved-Caspase-3 and Keap1 and enhanced the levels of SOD, GSH, CAT, Bcl-2, p62 and Nrf2. Conclusions: The results demonstrate that HES protects against ATO-induced cardiotoxicity, through inhibiting oxidative stress, and subsequent inflammation and apoptosis. The underlying results are closely related to the regulation of the p62-Keap1-Nrf2 signalling pathway.